Incentive contracts and efficient unemployment benefits - Dominique M. Demougin; Carsten Helm (Technische Universität Darmstadt, Department of Law and Economics, 2008)
Several European countries have reformed their labor market institutions. Incentive effects of unemployment benefits have been an important aspect of these reforms. We analyze this issue in a principal-agent model, focusing on unemployment levels and labor productivity. In our model, a higher level of unemployment benefits improves the workers' position in wage bargaining, leading to stronger effort incentives and higher output. However, it also reduces incentives for labor market participation. Accordingly, there is a trade-off. We analyze how changes in the economic environment such as globalization and better educated workers affect this trade-off.
Keywords: J65; D82; J41; E24; 330; Unemployment benefits; incentive contracts; Nash bargaining; moral hazard; globalisation; Arbeitslosenversicherung; Ökonomischer Anreiz; Berufliche Integration; Moral Hazard; Asymmetrische Information; Nash-Gleichgewicht; Institutionelle Infrastruktur; Globalisierung; Agency Theory